Income support for non-covered workers during COVID-19: A review of policy responses - Paul Marx; Werner Eichhorst; Ulf Rinne; Johannes Brunner (Institute of Labor Economics (IZA), 2022)
This paper provides an overview on the income support measures for non-covered workers implemented in response to the COVID-19 crisis, describing the collection of measures and policies in place in each selected country. This document provides a comparative overview of the different measures implemented in the context of the crisis, considering their design and evolution across the course of the crisis. In sum, there has been a worldwide wave of income transfers to support those hit hard by the pandemic. While the bulk of fiscal resources for these measures was (unsurprisingly) concentrated in high-income countries, there has been an impressive policy effort in middle- and low-income countries as well. Particularly the novel tools to identify potential beneficiaries and to distribute assistance is worthy of further research and evaluation. The sheer amount of policy activity should not blind us to the fact that responses were often insufficient to alleviate even the most extremes of poverty. In this sense, the pandemic is yet another reminder for how important investments in sustainable social protection systems, including infrastructures, in the global South will be for the future.
Keywords: I38; J08; J68; 330; income support; employment policy; economic policy; inequality; poverty; COVID-19; international comparison